Liderazgo en la gestión edil - Tomaylla, Maritza (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the Micaela Bastidas National University of Apurímac (Peru), whose objective was to determine the level of leadership of the municipal administration for the period 2018-2020, from the perspective of the citizens and servants of the municipality of Abancay (Peru). The findings of this study were based on a basic descriptive level research, within a non-experimental cross-sectional design, considering that objective results were sought, the approach was quantitative, for this purpose an appropriate questionnaire was developed for the public servant and another for the citizen that contains items for the dimensions of citizen security, public cleaning, execution of public works, and taxation system. These instruments were administered to a sample of 172 public servants between appointed and contracted, and 245 citizens, it being important to point out that the determination of the sample size was stratified probabilistic. For the contrasting of the hypothesis for being a comparative study with ordinal data, it was through the Mann Whitney U test whose inferential results allowed us to conclude that from the perspective of the citizen in 88% with respect to the leadership of the municipal management who point out that the leadership is not adequate, while public servants indicate that it is almost always or always adequate (53.9% and 23.26% respectively). The inferential analysis allows us to affirm that there is a significant difference between the perceptions of both groups.